Retaining older workers: the effect of phased retirement on delaying early retirement - Åsmund Hermansen (Nordic Journal of Social Research)
Introduction: Phased retirement involves reducing working time in the final years before retirement. The aim of phased retirement is to extend working careers and retain older workers who would otherwise opt for full early retirement. This article investigates the effect of offering phased retirement on early-retirement behaviour in Norway. Method: The data used in the analysis covers the period between 2000 and 2010 and comprises all employees between 61 and 62 years of age (N= 18 174) who were employed in any of the 442 companies that participated in a 2010 survey carried out by the Fafo Institute for Labour and Social Research and Respons Analyse AS, a Norwegian research firm. I use a difference-in-differences approach and logistic regression, which enables the measurement of changes in the individual relative risk of retiring full-time on the contractual pension (AFP, avtalefestet pensjon, contractual early-retirement pension,) before and after the introduction of phased retirement as a retention measure. Results: The results show that working in a company that offers reduced working hours for older workers does not have an effect on the relative risk of a 61- or 62-year-old withdrawing a full contractual pension in the next two years of their employment. This result is evident both before and after controlling for a range of known individual risk factors, as well as after controlling for company characteristics. Discussion: In the search for suitable measures for retaining older workers, offering phased retirement may still be part of the answer. Though my analysis does not support the idea that more flexible working hours is a decisive factor for those who choose to opt for full early retirement, a possible next step could be to investigate the impact of offering flexible working hours on the employment duration of those who do remain in employment.